Planning, Designing, Building, and Moving a Large Volume Maternity Service to a New Labor and Birth Unit: Commentary and Experiences of Experts. Issue 6 (November 2016) - VonBehren, Diane; Killion, Molly M.; Burke, Carol; Finkelmeier, Betsy; Zamora, Brigit
Abstract : Abstract: Three teams of perinatal expert nurses participated in planning and designing a new maternity unit, operationalizing the move to the new space, and evaluating care processes and workflows after the move. The hospitals involved were University of California, San Francisco Benioff Children's Hospital, Prentice Women's Hospital of Northwestern Memorial Healthcare in Chicago, IL, and Florida Hospital Orlando, Florida Hospital for Women. Although each team discussed specific details and lessons learned, there is remarkable consistency among the experiences of these teams and with the discussion of the process by the team at Mercy Hospital St. Louis published in this issue of MCN The American Journal of Maternal Child Nursing . Extensive planning, flexibility, involving key stakeholders, evaluating and simulating workflows, and adequate staffing and patient safety on move-day were reported to be essential to success. Reevaluation after settling in to the new unit and making changes as needed were discussed. Being part of the leadership team involved in planning and moving to a new maternity unit in what was likely a once-in-a-lifetime experience was viewed as a career highlight. Their commentary adds to what is known about planning and designing new maternity units, moving into the new space, and adjusting unit operations and care after making the new unit home. Abstract : Expert nurse leaders who participated in recent planning, design, building, and moving into a new women's hospital share their experiences with the process and offer advice to those who may be considering a move.